CHINESE CABBAGE BrMYB34.2 TRANSCRIPTION FACTOR REGULATES INDOLIC GLUCOSINOLATES BIOSYNTHESIS IN Arabidopsis - Ye Zhao; Yongqiang Zhang; Xianfeng Guo; Yan Ma; Peng Zhang; Hongling Liu; Gang Liu; Jing Guo (Acta Scientiarum Polonorum: Hortorum Cultus, 2020)
Glucosinolates (GS) are a group of sulfur- and nitrogen-rich plant secondary metabolites that originate from amino acids and exist mainly in plants in the order Brassicales, such as Arabidopsis thaliana (Arabidopsis) and Chinese cabbage (Brassica rapa ssp. pekinensis). To date, several regulatory components responsible for GS biosynthesis have been identified in Arabidopsis. However, the functions of GS biosynthesis regulators in Chinese cabbage have not been clarified. In our current study, a putative ATR1/MYB34 orthologous gene, BrMYB34.2, was isolated from Chinese cabbage leaves. To investigate the function of this gene, we engineered Arabidopsis plants that overexpress BrMYB34.2 ectopically and phenotypic analysis was performed. Moreover, we assayed the accumulation levels of indolic GS (IGS) and aliphatic glucosinolates in transgenic plants and test the expression of key genes of IGS biosynthesis and tryptophan synthesis by Real-time quantitative PCR. And further analysed the resistance of transgenic plants in 5MT stress treatment. The results indicate that ectopic expression of the BrMYB34.2 gene in Arabidopsis was able to up-regulate the accumulation level of IGS due to the increased expression of IGS and Trp biosynthetic genes. Moreover, overexpression of BrMYB34.2 conferred Arabidopsis 5MT resistance. These results suggest that the BrMYB34.2 gene may function as one of the regulators of IGS and Trp biosynthesis in Chinese cabbage.